Implementation of Learning Management In The Face of The Industrial Revolution 4.0 in STAI Bahriyatul Ulum Pandan - Nasution, Putra Mahendra Gunawan; Harahap, M. Rifai; Lubis, M. Syahdan; Mesiono, Mesiono (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to analyze the planning, implementation, and supervision of learning in the era of the industrial revolution 4.0 at STAI Bahriyatul Ulum Pandan. The research method used is a qualitative approach with descriptive research. The research was conducted at STAI Bahriyatul Ulum Pandan using data collection techniques through interviews and observations. The results of the study suggest that starting from the dominant competencies in the era of the industrial revolution 4.0, many inventions and successes of lecturers have been produced to improve the quality of learning in the form of curriculum development, and the use of technology, communication, and information in the application of various approaches and learning strategies. All innovative processes and successful learning are supported by the ability of lecturers to apply the principles of good learning management. The creeping industrial revolution 4.0 brings several challenges such as the loss of many jobs and the creation of new jobs, so skilled human resources are needed. As a religious institution, STAI Bahriyatul Ulum Pandan is expected to produce creative, imaginative, competent, and innovative graduates which can only be achieved by creating conducive learning conditions supported by learning management.